The Burial Landscape of Kos: From the Neolithic to the Roman Period - Dimakis, Nikolas (Ariadne, 2026)
This study provides an overview of the burial landscape of Kos from the Neolithic to the Roman period, highlighting key transformations in funerary practices and their cultural influences. The island’s strategic location facilitated interactions with neighboring regions, which shaped its evolving mortuary customs. In the Early Bronze Age, burial traditions included pit graves and pithos burials, transitioning to Mycenaean chamber tombs in the Late Bronze Age. During the Geometric period, both inhumation and cremation were practiced, with evidence suggesting cremation was linked to higher social status. By the Classical period, inhumation became dominant, and cemetery organization reflected urban planning principles. The Hellenistic period saw further expansion of cemeteries, with cist graves and rich funerary offerings, including figurines symbolizing rebirth, pointing to evolving beliefs in the afterlife. In the Roman era, burial architecture became more elaborate, with chamber tombs and loculi, reflecting increased social stratification. Despite external influences, local burial traditions persisted, demonstrating a blend of continuity and adaptation. The study underscores the importance of systematic archaeological publication and interdisciplinary research to fully understand the complex mortuary landscape of Kos within the broader ancient Mediterranean context.